COMPETITIVE ADVANTAGE OF LOCAL FRUIT SELLERS IN TOMOHON (CASE STUDY ON PASAR BERIMAN TOMOHON) - Kalangi, Nicky Sigar; Saerang, David P.E; Rumokoy, Farlane S. (Universitas Sam Ratulangi, 2018)
Abstract: Indonesia produces a variety of fruits, especially in North Sulawesi. The demand of fruit in Indonesia has increased by 10% over the last five years creating opportunities for people to sell local fruits at local farmers markets. In order for local fruit sellers to compete in the market, a strategy must be formed to gain competitive advantage. The objective of this study is to identify the competitive advantage of local fruit sellers in Pasar Beriman Tomohon. This research takes a qualitative approach by conducting interviews with 10 local fruit sellers in Pasar Beriman Tomohon as the respondents, which were chosen through purposive sampling and snowball sampling. The findings of this research are there are four variables that local fruit sellers in Pasar Beriman Tomohon consider to gain competitive advantage, which are factor conditions, demand conditions, related and supporting industries and company strategy, structure and rivalry. There are several similarities in factor conditions and related and supporting industries between the local fruit sellers and several differences in demand conditions and company strategy, structure and rivalry that are used as a competitive advantage. Local fruit sellers in Pasar Beriman Tomohon should form a strategy not only based on pricing but also services.Â Keywords: competitive advantage, strategic management, traditional market, qualitative study